STRUKTUR KEPEMILIKAN, USIA CEO DAN PRAKTIK MANAJEMEN LABA: STUDI PADA CONSUMER GOODS INDUSTRY - Andira Dzulkarnain; Nova Novita (Ibs Press, 2023)
The purpose of this research is to find the influence of family ownership, institutional ownership, and the age of CEO towards earnings management. The sample in this research are 30 manufacture companies from consumer goods industry. The sampling technique in this research using purposive sampling. By using panel data analysis we find that family ownership is not have any influence on earnings management. While the age of CEO and institutional ownership have the influence on earnings management.